2019
DOI: 10.1094/phyto-07-18-0245-fi
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control of Pierce’s Disease of Grape by an Endophytic Bacterium

Abstract: Effective preventive measures and therapies are lacking for control of Pierce’s disease of grape caused by the xylem-colonizing bacterium Xylella fastidiosa responsible for serious losses in grape production. In this study we explored the potential for endophytic bacteria to alter the disease process. While most endophytic bacteria found within grape did not grow or multiply when inoculated into mature grape vines, Paraburkholderia phytofirmans strain PsJN achieved population sizes as large as 106 cells/g and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 39 publications
5
40
0
Order By: Relevance
“…In addition, maintaining healthy microbiota and the presence of cultivar-specific microbes may support the resilience of the resistant olive cultivar Leccino to Xf infection [ 38 ]. This evidence was also confirmed in other pathosystems where experimental evidence suggests that plant colonization by specific bacterial endophytes is marked by a change in the expression of key genes in central metabolic and by priming expression of innate disease resistance pathways in plants that result in the reduction of disease [ 39 , 40 ]. At the same time, endophytic fungi can influence the plant’s metabolism by increasing the content of antioxidant compounds in the host [ 41 ].…”
Section: New Insights On Plant Response To X Fastidiosamentioning
confidence: 67%
“…In addition, maintaining healthy microbiota and the presence of cultivar-specific microbes may support the resilience of the resistant olive cultivar Leccino to Xf infection [ 38 ]. This evidence was also confirmed in other pathosystems where experimental evidence suggests that plant colonization by specific bacterial endophytes is marked by a change in the expression of key genes in central metabolic and by priming expression of innate disease resistance pathways in plants that result in the reduction of disease [ 39 , 40 ]. At the same time, endophytic fungi can influence the plant’s metabolism by increasing the content of antioxidant compounds in the host [ 41 ].…”
Section: New Insights On Plant Response To X Fastidiosamentioning
confidence: 67%
“…Concerning the priming concept, increased phytoalexin accumulation in leaves and stems of A. tumefaciens‐ inoculated plantlets after root treatments with Sn48 and Sa14 suggests a pathogen‐dependent activation of defence responses. In line with this concept, Baccari et al (2019) reported priming expression of the innate disease resistance pathway mediated by Paraburkholderia phytofirmans PsJN in grapevine inoculated with Xylella fastidiosa . Our findings revealed that Sn48 colonized grapevine roots but not aboveground plant parts, and enhanced trans ‐resveratrol, trans ‐piceid, and δ‐viniferin accumulation in all plant tissues of plantlets inoculated by A. tumefaciens .…”
Section: Discussionmentioning
confidence: 84%
“…PGPR-mediated ISR enhances the formation of physical barriers such as callose and lignin, the synthesis of plant defense chemicals as reactive oxygen species (ROS), phytoalexins and phenolic compounds (Benhamou, 1996; Samain et al, 2017), but certain PGPR do not induce PR proteins (Hoffland et al, 1995). On the other hand, the upregulation of genes, known as SAR pathway markers, such as PR2, chitinases and PR1 , have been observed with PGPR including the genera Bacillus, Pseudomonas, Paenibacillus , and Paraburkholderia (Park and Kloepper, 2007; Samain et al, 2017; Baccari et al, 2019). The overexpression of PR1 induced by PGPR might be explained by the abiotic stress as a response to root colonization by bacteria (Timmusk and Wagner, 1999).…”
Section: Introductionmentioning
confidence: 99%